LEGAL PROTECTION AGAINST CHILD EXPLOITATION IN THE DIGITAL ERA BASED ON THE PERSPECTIVE OF JUSTICE - Ngazis, Muhammad; Surahman, Surahman (fakultas hukum universitas PGRI Semarang, 2024)
This article discusses legal protection against child exploitation in the digital era which includes the legal basis, the role of the authorities, the challenges faced, as well as prevention and law enforcement efforts that can be taken. Child protection laws and laws regarding gambling crimes, human trafficking crimes, and human organ trafficking crimes provide the legal basis for child protection in the digital era. This research is normative legal research, using a statutory approach. This normative legal research is based on primary and secondary legal materials, namely research that refers to the norms contained in statutory regulations. library data collection method, or research in which the research object is explored through a variety of library information, including books, encyclopedias, scientific journals, and documents.in conclusion, protecting children from exploitation in the digital era is a formidable challenge that requires a multifaceted and evolving approach. It is only through the lens of justice—balancing prevention, protection, and prosecution—that we can hope to safeguard the innocence and rights of children in this increasingly digital world.